Contribution of the Educational Evaluation for the Democratic and Transformative Formation of the Student [Contribuição Da Avaliação Educacional Para a Formação Democrática E Transformadora de Estudantes] [Contribución de la Evaluación Educativa Para la Formación Democrática y Transformadora de Estudiantes] - Rios-Munoz, D; Herrera-Araya, D (Universidad Nacional, 2021)
Purpose. In this article, educational evaluation is analyzed as a theoretical-practical field of knowledge for the democratic and transformative formation of students. Discussion. The discussion on educational evaluation focuses on criticism of positivist-technological approaches limited to the value complexity of learning processes. Likewise, they have relieved evaluation approaches for learning as a way to question and reinterpret positivist evaluative theory and practice. However, the debate has marginalized the role of evaluation in its ethical-political dimension for the construction of democratic subjects. The central argument argues that a transformative evaluation with a sociocultural and democratic approach enables the formation of participatory, committed, and reflective subjects. Conclusions. It concludes with the importance of re-signifying the evaluation as a practice not only concerned with the valuation of learning but also oriented to the formation of aspects in terms of values and attitudinal, ethical, and democratic aspects, in order to contribute to the construction of students aware of themselves, of others, and their role in society. © 2021 Universidad Nacional. All rights reserved.